Relationship between Emotional Intelligence and Burnout in non-formal teachers of people with disabilities - Óscar Gavín-Chocano; Sonia Rodríguez-Fernández; David Molero; Inmaculada Molero-Martínez (Universidad Complutense de Madrid, 2022)
INTRODUCTION. The direct involvement of professionals who carry out their activity with people with Intellectual Disability can generate a high degree of stress and emotional exhaustion. The objective of this research was to evaluate the relationship between emotional intelligence and dispositional optimism in processes of professional Burnout. METHOD. One hundred forty-four subjects participated in this study, belonging to the Andalusian Association of Organizations in favor of people with Intellectual Disability (Spain). The following instruments were used: Life Orientation Test Revised, Trait Meta-Mood Scale-24 and Maslach Burnout Inventory. The reliability of the scores of each instrument (Cronbach's alpha and Omega coefficient), correlation between the scores in each of the dimensions, an analysis of differences of means (Student's t and ANOVA) based on the sociodemographic variables considered, is analyzed as well as a model of structural equations to determine the effects and relationships established by the different constructs under study. RESULTS. The results showed the positive relationship between some of the dimensions of burnout (emotional fatigue, personal fulfilment), emotional intelligence (repair) and dispositional optimism (p<.05). An analysis was performed using structural equations, concluding that the indicators with the greatest regression weight are the Burnout variables (depersonalization) and negatively (personal fulfillment). DISCUSSION. The discussion examines whether findings from the study follow the current trend in research conducted in this field. Among the main contributions of this investigation project is the fact that it is one of the first studies where Emotional Intelligence, Burnout and Dispositional Optimism in professionals of non-formal education of people with Intellectual Disabilities are included.